Membangun Kesadaran Sosial Melalui pilar-pilar pendidikan: Peran sekolah dalam masyarakat - Fitri, Maulida; Saurita, Kafifah; Gusmaneli, Gusmaneli (CV. ITTC INDONESIA, 2024)
This study explores the positive impacts of social awareness on students and its implications for community involvement. The research aims to identify the benefits of social awareness in shaping inclusive behavior, empathy, and leadership skills among students. A qualitative approach was used, combining literature review and case studies of school programs focused on social consciousness. Findings indicate that social awareness enhances students' ability to respect diversity, engage in social issues, and contribute positively to society. However, challenges such as individualism and limited institutional support are significant barriers to the effective implementation of social awareness programs. Strategies for overcoming these challenges include integrating social values into curricula, strengthening community service programs, and leveraging digital technology for social education.